The effectiveness of corpus-based training on collocation use in L2 writing for Chinese senior secondary school students - Fang Liuqin; Ma Qing; Yan Jiahao (Journal of China Computer-Assisted Language Learning)
Corpus tools are known to be effective in helping L2 learners improve their writing, especially regarding their use of words. Most corpus-based L2 writing research has focused on university students while little attention has been paid to secondary school L2 students. This study investigated whether senior secondary school students in China, upon receiving corpus-based training under the framework of data-driven learning (DDL), could improve their vocabulary use, especially the use of collocations, in their writing for the International English Language Testing System (IELTS) test. Twenty-two students aged 16–18 in a senior secondary school in Nanchang, China who were planning to take the IELTS exam participated in the study. Corpus of Contemporary American English (COCA) and Word and Phrase were the main corpora that the participants used to learn various search functions. Pre-writing and post-writing tests were administered to measure the effect of corpus training. In addition, a questionnaire and interviews were used to collect students’ perspectives and attitudes. The results indicate that students made improvement in word selection after three corpus training sessions, and their attitudes towards corpus use were positive even though they were restricted from using computers to access corpora inside their school.